The money launderers - Blunden, Bob. (Chalford, Gloucestershire : Management Books, 2001)
This book offers you a behind-the sceens look at one of the more mysterious but rapidly growing areas of organised crime.
Includes bibliographical references (p. 148) and index.
aug 24/05/13
Loans
Keywords: Money laundering -- Case studies; Money laundering -- Prevention; Organized crime -- Economic aspects; Money laundering